An idea of intuitive mobile diopter calculator for myopia patient - Komang Candra Brata; Mukhammad Sharif Hidayatulloh (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
The diopter is the unit of measurement for the refractive power of a lens. Myopia is a form of refractive error which is a leading cause of visual disability throughout the world. The prevailing treatment of refractive errors which are commonly used in daily life are glasses and contact lenses. Although those methods can overcome myopia, many myopia patients still don’t really know how to measure their current refractive error in diopter. This condition may retard the progression of refractive treatment in the myopic individual. The common methods to measure refractive error are phoropter with Snellen chart and retinoscopy, but those expensive tools need expertise to operate. This paper presents the concept of measure the face to smartphone screen distance to provide the possibility to implement a mobile application as a low-cost alternative refractive measurement tool. The main objective is to investigate the feasibility of mobile application to help patients with myopia measuring their blur line distances and evaluate their diopter levels independently. The experimental results reveal that, with 80.5 usability score the overall functionality of proposed application can be categorized as usable to users and feasible for future implementation.